Relationship between foreign direct investment inflows and Covid-19 pandemic in Pakistan: A monthly co-integration analysis - Ayesha Serfraz (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2022)
The global COVID-19 pandemic brought many challenges for the world including the downfall in foreign direct investment inflows (FDI). Although there are many other factors which cause a decline in FDI inflows in Pakistan but present study mainly focuses on COVID-19 pandemic as this resulted in closures of borders causing a sharp decline in FDI inflows. For this purpose, this study uses monthly data of Pakistan, starting from January 2020 (start of COVID-19 in Pakistan) till May 2022 (time period in which study has been conducted) to empirically analyze the relationship between FDI inflows and COVID-19. The results of ADF test statistic show that data is integrated of order (1). Johansen Co-integration approach is used to determine the relationship. Taking FDI inflows as a dependent variable and COVID-19 cases as an independent variable, the results suggest a linear co-integration relationship between these two variables with FDI inflows having a negative sign indicating a negative relationship between FDI inflows and COVID-19 cases. This study is innovative in the sense that it concentrates on finding a proper empirical relationship between FDI inflows and COVID-19 and does not focus only in analyzing existing figures. Empirical results suggest that Pakistan must devise such policies that can be implemented immediately in such unforeseen conditions as more and new variants are coming to surface. The availability of data puts a limitation on application of empirical technique since COVID-19 started in 2020 in Pakistan and the pandemic is still not over. In coming years, a time series analysis would be possible to carry a long run investigation. The co-integration technique is the most useful at the moment as it not only mentions the relationship between the variables during pandemic but also makes a future forecast.
Keywords: 330; COVID-19; Co-integration analysis; Unit root test; EViews; FDI inflows; Pakistan